Advances in enterprise engineering XIII : 9th Enterprise Engineering Working Conference, EEWC 2019, Lisbon, Portugal, May 20-24, 2019, Revised Papers /: 9th Enterprise Engineering Working Conference, EEWC 2019, Lisbon, Portugal, May 20-24, 2019, Revised Papers. (2020) - Unknown
No abstract available